2013
DOI: 10.4314/ahs.v13i2.26
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of diarrhoea among children below the age of 5 years in Sudan

Abstract: Background: The Millennium Development Goals recognise child health and survival as an important socio-development issue. Objective: To determine the correlates of diarrhoea among children aged below 5 years in north Sudan. Methods: We conducted secondary data analysis of the Sudan Multiple Cluster Indicators Survey II. Results: Altogether, 23,295 children were included in the survey. Half (50.0%) of the children were males, and 22.5% of them were of age less than one year. Boys were 3% (p=0.044) more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
53
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 14 publications
19
53
0
6
Order By: Relevance
“…This coupled with poor knowledge and practice of simple hygiene increase the risk of spread of disease to the under five children. The study respondent demonstrated good hygiene of hand washing after coming latrine, handling raw meat/ poultry, this study supports several other studies" [32]. The generally high prevalence of disease of them did not "changing baby's diapers, washing hand before cooking and they did not washing breast before breast feeding".…”
Section: Study Populationsupporting
confidence: 76%
“…This coupled with poor knowledge and practice of simple hygiene increase the risk of spread of disease to the under five children. The study respondent demonstrated good hygiene of hand washing after coming latrine, handling raw meat/ poultry, this study supports several other studies" [32]. The generally high prevalence of disease of them did not "changing baby's diapers, washing hand before cooking and they did not washing breast before breast feeding".…”
Section: Study Populationsupporting
confidence: 76%
“…The same study showed that drinking water sampled from Sokoto, a major town in this region was found to contain a very high load of microbes which were far beyond the allowable limits by WHO 2 . A study carried out in Sudan by Siziya et al 32 , also supports variation in diarrhea prevalence by geographic distribution.…”
Section: Discussionmentioning
confidence: 84%
“…This finding is corroborated by the study of Boardi and Keutunen 31 . However, according to Siziya, et al 32 , no relationship was established between wealth index and childhood diarrhea. In Nigeria, potable water as one of the key social responsibilities of the Government is either not available or not within the reach of the generality of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Use of unimproved toilet facilities and use of an unimproved source of drinking water increase children’s susceptibility to diarrhea [29, 30]. Besides, mother’s illiteracy and lower age (<25 years), the poor economic status of household and rural residence are also found to be associated with childhood diarrhea [19, 20, 2831]. …”
Section: Introductionmentioning
confidence: 99%